Persepsi Siswa tentang Komunikasi Interpersonal Guru di Sekolah Menengah Kejuruan Negeri 5 Padang - Riri Suliyarti; Nurhizrah Gistituati; Rusdinal Rusdinal; Irsyad Irsyad (Journal of Educational Administration and Leadership, 2020)
This study aims to determine: 1) students 'perceptions about openness of interpersonal communication of teachers, 2) students' perceptions of empathy in teacher's interpersonal communication, 3) students 'perceptions of supportive attitudes in teacher's interpersonal communication, 4) students' perceptions of positive attitudes of interpersonal communication of teachers, 5) students' perceptions about the similarity of teacher's interpersonal communication. This research is quantitative descriptive, and data collection techniques are using a questionnaire. The results showed that students' perceptions of teacher interpersonal communication were; 1) openness with 79.37% achievement which is in good enough criteria, 2) empathy with 86.80% achievement are in good criteria, 3) mutual support with 83.41% achievement in good criteria, 4) positive attitude with achievement of 79.67% in the category is quite good, 5) similarity with achievement of 76.67 in the criteria is quite good, so it can be concluded that the interpersonal communication of teachers in SMK 5 Padang according to students' perceptions with a score of 81.18% on good criteria.